2007
DOI: 10.1300/j030v15n04_07
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antioxidants on the Chemical and Sensorial Stability of Minced Jack Mackerel in Frozen Storage

Abstract: The effect of antioxidants on minced jack mackerel stored at Ϫ20ЊC for 90 days was evaluated. The antioxidants used were: ethylenediaminetetraacetic acid (EDTA), tert-butylhydroxiquinone (TBHQ), butylhydroxianisol (BHA), butylhydroxitoluene (BHT), and sodium erythorbate (SE) with or without sodium tripolyphosphate (STPP). Sensorial (taste, texture, and odor) and chemical (peroxide values, free fatty acids, fatty acids, and thiobarbituric acid) changes were evaluated during storage. The best results, by sensori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…FFA values of the controls and treated samples increased with storage time; by the end of the storage period (month 11), however, samples containing 1% BLO, TO, RO, BSO, SO, GSO, FSO and LO reached significantly (P \ 0.05) lower FFA value of 0.97, 1.59, 2.16, 1.45, 1.15, 1.06, 0.97 and 1.21% in comparison with the controls, which attained a higher level of 2.55%, respectively. Salas et al (2006) and Lugasi et al (2007) found lower contents of TBARS in synthetic (0.02% TBHQ) and natural antioxidant (rosemary extract) coated fish samples than those of the uncoated samples throughout the storage time.…”
Section: The Lipid Oxidation Of Frozen Chub Mackerelmentioning
confidence: 93%
“…FFA values of the controls and treated samples increased with storage time; by the end of the storage period (month 11), however, samples containing 1% BLO, TO, RO, BSO, SO, GSO, FSO and LO reached significantly (P \ 0.05) lower FFA value of 0.97, 1.59, 2.16, 1.45, 1.15, 1.06, 0.97 and 1.21% in comparison with the controls, which attained a higher level of 2.55%, respectively. Salas et al (2006) and Lugasi et al (2007) found lower contents of TBARS in synthetic (0.02% TBHQ) and natural antioxidant (rosemary extract) coated fish samples than those of the uncoated samples throughout the storage time.…”
Section: The Lipid Oxidation Of Frozen Chub Mackerelmentioning
confidence: 93%